Meninjau Angka Kasus Hipertensi di Puskesmas Lampisang Kecamatan Peukan Bada Kabupaten Aceh Besar - Defi Cintia Dewi; Muhammad Fikri; Eni Erlina; Farrah Fadhienie; Melania Hidayat; Dharina Baharuddin (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The working area of the Lampisang Community Health Center, Peukan Bada District, Aceh Besar Regency, has shown an increasing trend in hypertension cases over the past three years, making this disease the most common case treated. Hypertension is one of the main causes of morbidity and mortality due to non-communicable diseases, and is a significant burden both clinically and economically in various countries, including Indonesia. This study aims to conduct the implementation of the hypertension program at the Lampisang Community Health Center in 2022–2024 with a comprehensive evaluation approach that includes input, process, output, outcome, and impact. The evaluation was conducted using quantitative and qualitative descriptive approaches. Data were collected from Posbindu PTM forms, Community Health Center activity reports, and interviews with cadres and health workers. The analysis focused on service achievements, education effectiveness, therapy fulfillment, and long-term impacts on patients and the health care system. During 2022–2024, the number of hypertension patients increased from 320 to 404 cases. Blood pressure screening coverage reached 63.4% in 2024. The percentage of educated patients increased from 56.3% to 73.0%, and therapy adherence reached 62.6% in 2024. Outcomes showed that 64.0% of patients experienced a decrease in blood pressure and 59.0% made positive lifestyle changes. Long-term impacts showed improved early detection, but complications were still found in 36 cases over three years. Key challenges included limited facilities, low service coverage, and minimal village fund allocation for Posbindu (Community Health Post). The hypertension program at the Lampisang Community Health Center (Puskesmas) showed increasing achievements and outcomes year after year. However, program effectiveness still needs to be improved through strengthening facilities, ongoing education, and cross-sector collaboration to significantly reduce the prevalence and complications of hypertension.